Wall mural done by Shilo Shiv Suleman - Ghosh, Ayan (2023)
The Heritage Project draws attention to how women are integral to the growth and development of the Banganga neighborhood, and their role in sustaining ecology. Shilo Shiv Suleman depicts this interdependence with the use of a mix of text, portraits, and elements of Hindu mythology to create awareness and promote dialogue for social change.